2009
DOI: 10.1038/onc.2009.191
|View full text |Cite
|
Sign up to set email alerts
|

PML involvement in the p73-mediated E1A-induced suppression of EGFR and induction of apoptosis in head and neck cancers

Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase is commonly overexpressed in human cancers; however, the cellular mechanisms regulating EGFR expression remain unclear. p53, p63 and p73 are transcription factors regulating many cellular targets involved in controlling the cell cycle and apoptosis. p53 activates EGFR expression, whereas TAp63 represses EGFR transcription. The involvement of p73 in the regulation of EGFR has not been reported. Here, a strong correlation between EGFR overexpression and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…4) [53,59]. These data suggest a possibility that TA-p63γ/p73β, by inhibiting the expression of oncogenic EGFR, it could inhibit the TWIST expression, and thereby increase the E-cadherin expression [53,147]. This in turn will result in inhibition of EMT.…”
Section: Introductionmentioning
confidence: 83%
“…4) [53,59]. These data suggest a possibility that TA-p63γ/p73β, by inhibiting the expression of oncogenic EGFR, it could inhibit the TWIST expression, and thereby increase the E-cadherin expression [53,147]. This in turn will result in inhibition of EMT.…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have reported that BaP‐induced apoptosis is associated with the p53 signaling pathway in several cell lines (Ko et al,2004; Mansoor et al,2009; Tekpli et al,2009). p73 closely mimics p53 and induces apoptosis (Klanrit et al,2009). They are each activated by different types of DNA damage (Bergamaschi et al,2004; Rocco et al,2006) and are both involved in the apoptotic response to p53‐null cells treated with certain genotoxic agents (Ramadan et al,2005).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the position of the amino group in 5‐ASA benzene ring is critical for improvement of replication fidelity 21 . As p53 activates epidermal growth factor receptor (EGFR) expression in cancer cells 22 and EGFR function is required for cell cycle progression 23,24 there are many reasons to suggest a connection between 5‐ASA‐mediated phosphorylation of p53 and EGFR status. Findings of Monteleoni’s group show 5‐ASA inhibition of EGFR signalling pathway by enhancing activity of SH‐PTP2 phosphatase 25 .…”
Section: Methodsmentioning
confidence: 99%